Impact of whey protein isolate and eccentric training on quadriceps mass and strength in patients with anterior cruciate ligament rupture: A randomized controlled trial - Xiaoyuan Zhang; Hongshi Huang; Yuanyuan Yu; Jie Yang; Zixuan Liang; Cuiqing Chang
Objective: To examine the effects of combining whey protein isolate supplement with preoperative isokinetic eccentric training on quadriceps mass and strength following anterior cruciate ligament rupture. Design: Randomized controlled trial. Subjects: A total of 37 male subjects with anterior cruciate ligament rupture. Methods: Participants were randomly assigned to an isokinetic eccentric training group (n = 19) or an isokinetic eccentric training + whey protein isolate group (n = 18). Both groups received isokinetic eccentric training for 6 weeks. The isokinetic eccentric training + whey protein isolate group received 22 g whey protein isolate daily. Results: After the intervention, the cross-sectional area of the affected quadriceps had increased only in the isokinetic eccentric training + whey protein isolate group (7.6 ± 6.8%; p = 0.012), whereas there was no change in the isokinetic eccentric training group (3.7 ± 4.5%; p = 0.11). Both groups showed increased quadriceps strength; however, there were no further effects for the isokinetic eccentric training + whey protein isolate group. Lysholm and IKDC 2000 knee function scores increased only in the isokinetic eccentric training + whey protein isolate group (p < 0.01). Conclusion: Although the study showed numerically better outcomes for the combination of whey protein isolate supplement with isokinetic eccentric training compared with isokinetic eccentric training alone, no statistically significant differences were demonstrated between the groups.